PENINGKATAN PRESTASI BELAJAR MATEMATIKA PADA SISWA MELALUI IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Eka Marhaeni Wraswati, Luh Putu (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
This research was conducted in Class IX-6 of Singaraja 2 Public Middle School in the odd semester of the 2017/2018 school year, with an average condition of only 59.21. This condition did not meet the minimal expected score. The percentage of achievement has only reached 28.95%. The purpose of writing this class action research is to improve Mathematics achievement through the implementation of Problem Based Learning Learning Models. The data was collected through tests, which were then analyzed using quantitative descriptive methods. Data was presented in the form of average learning achievement and completeness learning process. The results obtained from this study were the development of very positive results. Initially on average; 59.21 with learning completeness only; 28.95%, then after the implementation of Cycle I increased to an average of 73.68 with learning completeness reaching 55.26% From Cycle I to Cycle II there was also an increase which reached an average of 76.32 and completeness of learning 86.84 %. The conclusion obtained from this study is the Implementation of Learning Based Learning Model can improve the mathematics achievement of students in class IX-6 of Singaraja 2 Public Middle School in the semester of school year 2017/2018. Keywords ; problem based learning model, improvement in learning mathematics